2011
DOI: 10.1111/j.1540-8175.2011.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Aortic Elastic Properties in Patients with Chronic Graft-versus-Host Disease

Abstract: Aortic stiffness measurements were significantly different in chronic GVHD group compared to non-GVHD group and these findings suggested useful explanation for the potential mechanism about the development of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(90 reference statements)
0
0
1
Order By: Relevance
“…To our knowledge, our present study is the first to study directly the mechanical properties of mesenteric resistance arteries in acute GVHD. In chronic GVHD, a study in humans evaluated the compliance of the aorta via ultrasound [43]. In contrast to our study, they found an increased arterial stiffness in patients with disease duration of about 15 months.…”
Section: Endothelial Dysfunction In Gvhdcontrasting
confidence: 99%
“…To our knowledge, our present study is the first to study directly the mechanical properties of mesenteric resistance arteries in acute GVHD. In chronic GVHD, a study in humans evaluated the compliance of the aorta via ultrasound [43]. In contrast to our study, they found an increased arterial stiffness in patients with disease duration of about 15 months.…”
Section: Endothelial Dysfunction In Gvhdcontrasting
confidence: 99%